Pin Transfer Of Epoxy Resin (Glycerin) On The Led Housing - Chandhira, Gajjhenthra Richard Raj @ (Universiti Sains Malaysia, 2019)
LED Technology has been implemented in so many daily applications and is still being improvised in so many aspects. The key feature in a complete working LED model is the whole LED setup within itself. A lot of problems are arising and being studied regarding the LED setup. The main aim of my research is to solve the epoxy transfer on to the LED Housing. The problem faced in the industry is that a hemispherical shaped epoxy is formed on the LED Housing after the transfer which damages the housing. Thus, simulation using ANSYS Fluid Structural Interaction (FSI) is carried done along with pin transfer experiment to validate each other’s result. The results obtained from the ANSYS simulation would be velocity contour and pressure contour and from the experiment, the transfer of the epoxy from the pin to the LED Housing can be witnessed. My motive is to achieve a thin layer epoxy on the LED Housing after the transfer and see if it agrees with the simulation results.